Automatic Evaluation of the Mechanical Properties of Steels Maraging using Digital Image Processing Techniques - Viana, Angélica Alves; Rabelo, Savio Lopes; Santos, José Daniel de Alencar; Filho, Venceslau Xavier de Lima; Rodrigues, Douglas de Araújo; Ivo, Roberto Fernandes; Rebouças Filho, Pedro Pedrosa (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2020: Anais Estendidos da XXXIII Conference on Graphics, Patterns and Images, 2020)
Some strategic sectors of the economy require that the raw material of their machines and equipment have mechanical properties that satisfy their use. Maraging steel is a material of great concern since it is necessary to have a high mechanical resistance associated with high fracture toughness. The traditional tests to determine the fracture toughness of this material before use in applications are the Charpy and KIC tests. However, this process is characterized by being exhaustive and requiring specialized and trained professionals. Thus, to reverse this situation, this work proposes a new approach to determine the mechanical properties of maraging steel. For this, initially, the method removes any artifacts present in the image resulting from the mode of acquisition. In sequence, this works tested the method Extended Minimum Transformation (EMT) and mathematical morphology to find these markers of the regions of the dimples. Then, the Adaptive Thresholding, Optimal Global Thresholdusing the Otsu Method and Watershed transformation methods were used to segment the dimples. In the end, the diameter of the dimples and the toughness of the material were calculated. Tests are carried out and compared with the result obtained by specialists using the traditional system to evaluate the proposed approach. The results obtained were satisfactory for the application because the proposed approach presented speed and precision to the conventional methods.